“For normal people, it just doesn’t work”: uncovering popular lenses on environmental sustainability in The Netherlands - Kjell Noordzij; Joost Oude Groeniger; Willem de Koster; Jeroen van der Waal (Sustainability: Science, Practice, & Policy)
Governments grapple with garnering public support for the interventions they propose to achieve with respect to environmental sustainability. We depart from the position that interventions for these issues must align with public perspectives to receive support among the population at large. Our study uses 14 focus-group interviews (n = 57) conducted in the Netherlands to inductively explore these perspectives on a wide range of sustainability issues and their interventions. Our sample predominantly comprises individuals who have not completed tertiary education. As extant research suggests, these individuals are less concerned with sustainability issues. We identify three lenses through which our respondents perceived sustainability, namely how it: 1) impacts their personal life (lens of need); 2) aligns with their community (lens of community); and 3) raises doubts (lens of doubt). They reveal that many respondents are principally engaged with sustainability in ways that they felt had practical repercussions for them or their community. We conclude by instigating a rethinking of inclusive sustainability interventions by sensitizing them to the perspectives individuals have of sustainability issues and interventions, and those of non-tertiary educated individuals in particular.